The Intervertebral Disc Molecular and Structural Studies of the Disc in Health and Disease - Shapiro, Irving M.; Risbud, Makarand V. (Springer Vienna : Imprint: Springer, 2014)
The intervertebral disc is composed of a complex tissue that separates neighboring vertebrae, permits a wide range of motion, and cushions the high biomechanical forces on the spine. Disc degeneration leads to a loss of function and is often associated with excruciating pain. Written by leading scientists and clinicians, this is the only book in the past fifty years devoted entirely to the study of the intervertebral disc. The first part of the book provides a review of the basic biology of the disc in health and disease. The second part considers strategies for mitigating the effects of disc degeneration and discusses the possibility of engineering replacement tissues. The final section is dedicated to approaches that model normal development, and the elucidation of the pathogenesis of degenerative disc disease using animal, organ and cell culture techniques.  This unique and authoritative book bridges the gap between the basic and clinical sciences; its target audience includes basic scientists, orthopedists, neurologists, rehabilitation and physical therapists, primary care physicians and chiropractors, while it also addresses the needs of graduate students, medical students, interns, fellows, and patients who suffer from disc-related pathologies.